Nursery container studies on Acacia galpinii, A. karroo and Bolusanthus speciosus - Motoma, Lesego M.(Lesego Motlatsi) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.